Numerical study of irregular breaking wave forces on a monopile for offshore wind turbines. (October 2017) - Aggarwal, Ankit; Chella, Mayilvahanan Alagan; Bihs, Hans; Arntsen, Øivind Asgeir
Abstract: The substructures of offshore wind turbines are subjected to different types of hydrodynamic loads from sea states. The wave forces exerted by irregular breaking waves are one of the serious concerns because of the uncertainties involved in defining the breaking wave and the resulting force calculations. In the present study, irregular breaking wave forces on a vertical pile structure are investigated using an open-source Computational Fluid Dynamics (CFD) model REEF3D. The Level Set Method (LSM) is used for modelling the free surface. The Bretschneider spectrum is used for the irregular wave generation. This is validated in the numerical wave tank by comparing the numerical wave spectrum with the experimental wave spectrum. The wave free surface is calculated at three wave gauge locations and compared with experiments. It is observed that the peak of spectral wave density is higher for the wave gauge located besides the cylinder due to shoaling, wave run up and reflections from the cylinder and the peak of spectral wave density is lower for the wave gauge located behind the cylinder due to wave breaking. Further, simulations are performed to study the wave forces on a monopile due to the depth-limited breaking waves. A good match is observed with the experimental and numerical results. Numerical wave energy spectra at different locations along the tank are compared to study the changes in the wave surface elevations due to the interaction of irregular breaking waves with a monopile. The statistical parameters for free surface elevation and wave forces are further investigated. The free surface features around the monopile during its interaction with waves are also studied.